Non-tariff measures and sustainable development in Kazakhstan and Kyrgyzstan - Zalina Enikeeva (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
This study analyses the relationship between non-tariff measures (NTMs) applicable in the agricultural sector of Kazakhstan and Kyrgyzstan and the sustainable development goals (SDGs). Kazakhstan and Kyrgyzstan, as newer members of the Eurasian Economic Union (EAEU), first established by Belarus, Kazakhstan and the Russian Federation in 2010, have the intention of eliminating intra-block barriers in the trade of goods, services, capital and labour. Elimination of barriers, as envisaged by the EAEU Treaty, specifically includes non-tariff regulation. However, the scope of non-tariff regulation, as defined in the Treaty, only includes traditional commercial instruments, such as licencing and quotas. Other regulations which are considered as NTMs by WTO, UNCTAD and other international organizations, such as sanitary and phytosanitary measures and technical barriers to trade, are addressed by other chapters in the Treaty and are not subject to elimination. As such, there is sometimes confusion in discussions about NTMs within the scope of the EAEU due to such varying definitions. Many NTMs (in broader sense) in Kazakhstan and Kyrgyzstan are found to have legitimate and necessary objectives, such as protection of human, animal and plant health or, protection of the environment. At the same time, there seems to have been instances in the region of NTMs being overtly used with a protectionist intent. The bulk of the measures examined affecting agricultural trade, however, showed that the most frequent NTMs might be addressing health-related Sustainable Development Goals. Data on NTMs remain incomplete in many countries of the region. This is evident by the varying level of completeness of measures notified by EAEU member States to the WTO that are based on ratified EAEU regulations. As such, further efforts are needed to increase transparency in this area to ensure the measures do not create unnecessary barriers to trade and sustainable development.
Keywords: F1; F13; O24; 330; non-tariff measures; EAEU; Kyrgyzstan; Kazakhstan; trade in agricultural products; sustainable development